Clinical practice of early screening and risk-stratified management for oral potentially malignant disorders - Ge, Beibei; Zhu, Xinqiang; Ma, Meimei; Ju, Yingxin; Ma, Yannan; Song, Yong (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the application value of standardized screening and risk-stratified management in the clinical practice of Oral Potentially Malignant Disorders (OPMDs) for improving early diagnosis rates and optimizing intervention strategies.MethodsA total of 312 OPMD patients diagnosed between January 2017 and December 2022 were enrolled. A screening pathway of “initial screening (questionnaire + visual/tactile examination) - refined screening (pathological biopsy)” was established. Risk stratification (low, intermediate, high) was performed using a modified Proliferative Verrucous Leukoplakia (PVL)-based scoring system. Multidisciplinary team (MDT) management was implemented. Risk factors for malignant transformation were analyzed using Cox regression.ResultsThe high-risk group had a significantly higher malignant transformation rate than the intermediate and low-risk groups (12.5% vs. 3.5% vs. 0%, P<0.001), with a shorter median time to transformation (23.4 months). Severe epithelial dysplasia (HR = 6.24), lesions located in the tongue ventral/floor of mouth (HR = 3.34), and betel quid chewing history (HR = 2.62) were identified as independent risk factors. The MDT model achieved a 2-year cancer-free survival rate of 91.4% in high-risk patients and improved follow-up compliance to 83.3%.ConclusionAn OPMD management model based on risk stratification and MDT collaboration can effectively identify high-risk patients, optimize intervention timing, and improve prognosis. This model is suitable for promotion in primary care hospitals.